Study on the Interaction between Cadmium Sulphide Nanoparticles and Proteins by Resonance Rayleigh Scattering Spectra - Weiwei Zhu; Qi Wang; Dan Su (Journal of Chemistry)
The interaction of cadmium sulphide nanoparticles [(CdS)n] with proteins has been studied by resonance Rayleigh scattering spectra (RRS). Below the isoelectric point, proteins such as bovine serum albumin (BSA), human serum albumin (HSA), lysozyme (Lys), hemoglobin (HGB), and ovalbumin (OVA) can bind with CdSn to form macromolecules by virtue of electrostatic attraction and hydrophobic force. It can result in the enhancement of resonance Rayleigh scattering spectra (RRS) intensity. Their maximum scattering peaks were 280 nm, and there was a smaller peak at 370 nm. The scattering enhancement (ΔIRRS) is directly proportional to the concentration of proteins. A new RRS method for the determination of trace proteins using uncapped CdSn nanoparticles probe has been developed. The detection limits are 19.6 ng/mL for HSA, 16.7 ng/mL for BSA, 18.5 ng/mL for OVA, 80.2 ng/mL for HGB, and 67.4 ng/mL for Lys, separately. In this work, the optimum condition of reaction, the effect of foreign, and the analytical application had been investigated.